Pengolahan Isyarat Jantung Berbasis Wavelet Untuk Deteksi Kelainan Infark Menggunakan Metode High Speed Qrs Detection - Widodo, Bernarditus Sri (Jurnal GEMATIKA, 2009)
A high precision is generally required by doctors in order to read the ECG records presented in the scaled paper. This research is conducted in order to realize a prototype which could help the doctors in the interpretation of ECG records for infarction detection. This research processes the already existing ECG records using wavelet noise elimination technique, which is then analyzed by using High Speed QRS Detection method in order to obtain some parameters of Q-Pathological wave as well as the elevation value of the ST segment. The final result is the detection of myocardial abnormalities, which is presented visually by using graphical user interface, working well.